2010
DOI: 10.1177/0095399709349695
|View full text |Cite
|
Sign up to set email alerts
|

Representative Bureaucracy and Policy Tools

Abstract: This article examines how racial and ethnic representation influences the tools that public officials use in designing policy. We use Schneider and Ingram's policy tools framework to empirically test how racial and ethnic representation affects student discipline outcomes in a sample of Georgia public schools. We find that schools with balanced racial and ethnic representation are more likely to adopt learning-oriented discipline policies, whereas those with imbalanced representation are more likely to impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Variations in the attitudes of principals shape the rates of exclusionary discipline, and the evidence suggests that principals who consider the context and have a clear philosophy that guides discipline use exclusionary discipline less often relative to principals who strictly adhere to disciplinary policy (Mukuria, 2002). Teachers’ classroom management skills (Skiba, Chung, et al, 2014), teacher–student racial match (Bradshaw, Mitchell, O’Brennan, et al, 2010; Jordan & Anil, 2009; Kinsler, 2011; Lindsay & Hart, 2017), the lack of a representative bureaucracy (Blake, Smith, Marchbanks, Seibert, & Kim, 2016; Feistritzer, Griffin, & Linnajarvi, 2011; Grissom, Nicholson-Crotty, & Nicholson-Crotty, 2009; Meier, 1993; Meier & Stewart, 1992; Roch, Pitts, & Navarro, 2010; Rocha & Hawes, 2009; Staats, 2014), and teachers’ perceptions, expectations, and bias (Bradshaw, Mitchell, O’Brennan, et al, 2010; Carter et al, 2017; Gershenson & Dee, 2017; Golann, 2015; Gregory & Mosely, 2004; Gullo, 2017; Hines-Datiri, 2015; McNeal, 2016; Okonofua, Walton, & Eberhardt, 2016; Skiba et al, 2011; Staats, 2014) also play a critical role in the disciplinary process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in the attitudes of principals shape the rates of exclusionary discipline, and the evidence suggests that principals who consider the context and have a clear philosophy that guides discipline use exclusionary discipline less often relative to principals who strictly adhere to disciplinary policy (Mukuria, 2002). Teachers’ classroom management skills (Skiba, Chung, et al, 2014), teacher–student racial match (Bradshaw, Mitchell, O’Brennan, et al, 2010; Jordan & Anil, 2009; Kinsler, 2011; Lindsay & Hart, 2017), the lack of a representative bureaucracy (Blake, Smith, Marchbanks, Seibert, & Kim, 2016; Feistritzer, Griffin, & Linnajarvi, 2011; Grissom, Nicholson-Crotty, & Nicholson-Crotty, 2009; Meier, 1993; Meier & Stewart, 1992; Roch, Pitts, & Navarro, 2010; Rocha & Hawes, 2009; Staats, 2014), and teachers’ perceptions, expectations, and bias (Bradshaw, Mitchell, O’Brennan, et al, 2010; Carter et al, 2017; Gershenson & Dee, 2017; Golann, 2015; Gregory & Mosely, 2004; Gullo, 2017; Hines-Datiri, 2015; McNeal, 2016; Okonofua, Walton, & Eberhardt, 2016; Skiba et al, 2011; Staats, 2014) also play a critical role in the disciplinary process.…”
Section: Resultsmentioning
confidence: 99%
“…Using both survey and U.S. Census data, Rocha and Hawes (2009) found that the presence of minority teachers and racial/ethnic diversity within districts contributed to lower levels of discrimination and that schools with a representative and diverse teaching force had smaller racial discipline disparities. Roch et al (2010) used school demographic data, discipline records, and a linear pooled model to explore the correlations between bureaucratic representation and discipline philosophies and found that schools with a diverse teaching force employed less punitive disciplinary practices and relied on rehabilitative approaches. Blake et al (2016) analyzed a statewide data set of three 7th-grade cohorts over 5 years, using binomial logistic regression to determine whether student–teacher racial/ethnic matches accounted for students’ risk for exclusionary sanctions (in-school suspension, OSS, alternative placement, or expulsion) and found that the risk of receiving any type of sanction increased in schools where the faculty and students were less similar racially and ethnically.…”
Section: Resultsmentioning
confidence: 99%
“…Passive representation has been found to lead to active representation when the bureaucrat represents the interests of the client and takes actions that benefit the individual client (Nicholson-Crotty et al 2016), when the bureaucrat advocates for changes in organization policies that benefit the represented group (Roch, Pitts and Navarro 2010), and through contagion effects where the presence of the minority bureaucrat changes the behavior of other bureaucrats, which benefits minority clientele (Atkins and Wilkins 2013). Subsequent literature separately identifies symbolic representation to occur when passive representation changes the attitudes or behaviors of individuals who are represented, thereby enhancing outcomes independent of any bureaucrat's action (Riccucci, Van Ryzin, and Lavena 2014;Riccucci, Van Ryzin, and Jackson 2018;Theobald and Haider-Markel 2008).…”
Section: Representative Bureaucracymentioning
confidence: 99%
“…For example, Soss (1999) insurance program (Social Security Disability Insurance [SSDI]) to explore the links between welfare participation and broader forms of political involvement, evidencing that policy designs structure clients' program experiences in ways that teach alternative lessons about government nature. Roch, Pitts, and Navarro (2010) examined how racial and ethnic representation influences public officials' tools in designing policy in a sample of Georgia public schools. They found that schools with balanced racial and ethnic representation are more likely to adopt learningoriented discipline policies, whereas those with imbalanced representation are more likely to implement sanction-oriented policies.…”
Section: Cluster 8: Interaction Representation and Their Influence On...mentioning
confidence: 99%